Power play : a novel - Steel, Danielle (Delacorte Press, 2014)
A high-powered CEO and mother of two, a mom who gave up a promising law career, and a struggling artist and mother with an absent husband are forced to reevaluate their sacrifices and beliefs when they confront the realities of power and family.